2002
DOI: 10.1051/forest:2002009
|View full text |Cite
|
Sign up to set email alerts
|

Rapid seedling obtaining from European ash species Fraxinus excelsior (L.) and Fraxinus angustifolia (Vahl.)

Abstract: -Three different dissection treatments were applied to mature seeds of two European ash species: Fraxinus excelsior (L.) and Fraxinus angustifolia (Vahl.) in order to compare their relative efficiency for germination and further development. The in vitro embryo culture appeared to be the most efficient for both species (nearly 90% of viable plants). The two species expressed differences in germination rate without embryo culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 11 publications
1
37
0
Order By: Relevance
“…[16,19]) is well documented, and some studies had pointed out differences in the strength of dormancy between the two species [16]. Raquin et al [19] compared the relative efficiency of germination of F. excelsior and F. angustifolia (with seed samples from one population of each species), applying three different treatments and suggested that germination tests can be potentially used as a first test to separate the two species. The embryo/seed size ratio gives a first measure of the underdevelopment of the embryo, and this character is known to be involved in germination ability and evolution of seed dormancy [1,2,12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[16,19]) is well documented, and some studies had pointed out differences in the strength of dormancy between the two species [16]. Raquin et al [19] compared the relative efficiency of germination of F. excelsior and F. angustifolia (with seed samples from one population of each species), applying three different treatments and suggested that germination tests can be potentially used as a first test to separate the two species. The embryo/seed size ratio gives a first measure of the underdevelopment of the embryo, and this character is known to be involved in germination ability and evolution of seed dormancy [1,2,12].…”
Section: Introductionmentioning
confidence: 99%
“…[17,24]) or both (e.g. [16,19]) is well documented, and some studies had pointed out differences in the strength of dormancy between the two species [16]. Raquin et al [19] compared the relative efficiency of germination of F. excelsior and F. angustifolia (with seed samples from one population of each species), applying three different treatments and suggested that germination tests can be potentially used as a first test to separate the two species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both species, the fruit consists of winged seeds (samaras) that are dispersed by wind. In continental Europe, F. angustifolia usually flowers a few months earlier than F. excelsior (Raquin et al, 2002b;Jato et al, 2004). However, an overlap in flowering times of the two species has been recorded in the Loire hybrid zone (France), but in this case assortative mating produces significant genetic isolation (Gérard et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…Seeds were air-dried for 2 weeks at room temperature, rehydrated slightly overnight in water at 4 1C, immersed in 0.3 M NaOH at room temperature for 20 min and then sterilized for 2 h in calcium hypochlorite (70% active chlorine) at 4 1C (Raquin et al, 2002b). Seed wings were removed and the seeds were checked for the presence of whole embryos using a stereomicroscope.…”
Section: Dna Extraction and Genotyping Of Microsatellite Markersmentioning
confidence: 99%